ИДЕНТИФИКАЦИЯ ЛИНЕЙНОЙ ОБОБЩЕННОЙ НАГРУЗКИ В ЗАДАЧЕ РАСПРЕДЕЛЕНИЯ ФАКТИЧЕСКИХ ВКЛАДОВ В ИСКАЖЕНИЯ НАПРЯЖЕНИЙ В ТРЕХФАЗНЫХ ЧЕТЫРЕХПРОВОДНЫХ СЕТЯХ - Саенко, Ю.Л.; Калюжный, Д.Н.; Свергуненко, С.В. (Інститут електродинаміки НАН України, Київ, 2018)
For an adequate representation of the mix load distribution in the mathematical models of factual contributions necessary to determine the structure of its equivalent circuit and method of calculation of its parameters. On the basis of the matrix method of electrical circuits analysis to determine the structure of the equivalent circuit of substitution of mix loads. Defining the parameters of the equivalent circuit of substitution mix load in the framework methodology for measuring indicators of power quality index is practically not feasible. An approximate equivalent circuit of the mix load, the parameters of which can be determined by the results of individual measurements. The analysis of errors in determining the approximate equivalent circuit of the mix load in relation to the problem of the distribution of factual contributions to the distortion of the voltage symmetry at the point of common coupling.  References 7, table 1, figures 4.